Komunikasi Perempuan dalam Dakwah (Menciptakan Ruang untuk Representasi dan Kepemimpinan) - Tamim, Rouf; Isti'ana, Ais; Suslina, Suslina (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study explores the leadership role of women in da'wah with a focus on representation and transformational leadership. This study uses desk research methods to analyse relevant literature, with the aim of understanding how the representation of women in various forms of da'wah communication-such as lectures, writings, and social media-can influence people's perceptions of women's leadership capabilities. The research findings show that strong and positive representations of women in da'wah can change people's perceptions and open up opportunities for women to take on leadership roles. Key challenges faced in creating space for women's representation and leadership include persisting patriarchal norms, resistance from conservative parties, and limited access and resources. This analysis highlights that women's transformational leadership, characterised by a clear vision, attention to the individual, intellectual stimulation, and idealised influence, has great potential to bring about positive change in religious communities. The impact of this transformational leadership includes changing gender perceptions and stereotypes, increasing community participation, empowering individuals, and enhancing innovation and creativity. By addressing these challenges and supporting women's transformational leadership, religious communities can become more inclusive, just and dynamic. This research confirms the importance of strong representation and support for women in da'wah leadership to achieve significant social and cultural change.